The Relations of Science Task Values, Self-Concept of Ability, and STEM Aspirations Among Finnish Students From First to Second Grade - Vinni-Laakso, Janica; Guo, Jiesi; Juuti, Kalle; Loukomies, Anni; Lavonen, Jari; Salmela-Aro, Katariina (Frontiers in Psychology, 2019)
According to modern expectancy-value theory, students’ motivation in school subjects begin to vary at the very beginning of their school careers, showing a task-specific pattern of motivation. However, there is no clear evidence in the literature on how students’ value beliefs are formed and interact with each other in early elementary schools. Using the longitudinal structural equation modeling, this study examined relations between science-related task values (i.e., intrinsic value and cost), self-concept of ability, and future occupational aspirations based on first graders and one-year follow-up from seven schools in the Helsinki (N = 332; ages = 7 and 8; girls = 51%). Results showed that the students who had a high science-related self-concept of ability and intrinsic value tended to perceive low cost of science learning. Science-related self-concept of ability were the most stable construct, while in intrinsic value, and cost there were significant levels of fluctuation across the first and second grades. A high science-related self-concept of ability in the first grade predicted a lower cost value in the second grade, and a high science-related intrinsic value was a marginally significant predictor of future occupational aspirations in science, technology, engineering, and mathematics (STEM). Mean-level differences revealed that the girls’ science-related self-concept of ability, intrinsic value, and cost remained the same in both grades, while the boys’ self-concept of ability decreased. The girls’ mean levels in science-related intrinsic value were higher than those of the boys, while students’ self-concept of ability and cost were similar across gender in both grades. A cross-lagged panel model revealed that the girls reported more STEM occupational aspirations than the boys in the second grade, while controlling for the motivational beliefs. In summary, the results indicate that a high-level of science interest in young students predicts STEM occupational aspirations; high girls’ intrinsic value in early science education do not steer them away from STEM occupations; boys’ task motivation might be at greater risk of decline during early science education.